Transition in electronic transport properties of graphene nanoribbon due to the adsorption of atoms and molecules - Shakil, Shifur Rahman; Saha, Atanu Kumar; Bhuian, Md. Belal Hossain (© 2015 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 10th IEEE International Conference on Nano/Micro Engineered and Molecular Systems, NEMS 2015; Xi'an; China; 7 April 2015 through 11 April 2015 [© 2015 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http://10.1109/NEMS.2015.7147447